Potensi Pesantren Sebagai Destinasi Wisata Halal Baru di Indonesia - Lailatul Qadariyah (Fakultas Ekonomi Universitas Yos Soedarso, 2019)
Pesantren is the oldest religious education institution in Indonesia. The education system and method applied are the strengths to produce experts in the field. In recent years the pesantren has not only focused on the study of religious knowledge but also other fields so it is not surprising that public interest continues to increase and not a few people are increasingly curious about the pesantren. This then becomes one of the reasons why pesantren should be considered as a tourist destination. Therefore the study of the potential of pesantren that can be